Comparison of microscopic and endoscopic views in cadaveric ears - Guy, John (Eur Arch Otorhinolaryngol, 2020)
PURPOSE: The advent of endoscopic otosurgery provides reduced tissue destruction with theoretically improved views, yet a quantification of the difference of exposure between microscopic and endoscopic approaches has not yet been performed in human specimens. The objective of this study was to assess the difference in views of cadaveric tympanic membranes when inspected with operating microscopes or endoscopes. METHODS: A circular graduated disc was inserted into eight cadaveric external ear canals to rest against the tympanic membrane. Three independent observers assessed the maximum possible observable radius of the graduated disc in each ear using a 0° endoscope and a surgical microscope in superior, inferior, posterior, and anterior directions. RESULTS: The endoscope was able to view a significantly larger mean maximum visible radius than the microscope in posterior, superior, anterior, and inferior directions. This represented a mean gain in observable distance of 19.18%. There was a smaller variation in mean maximum visible radius than the microscope. CONCLUSION: The wider field of view in an endoscope compared to a microscope implies reduced surgical tissue damage is needed to provide sufficient operative exposure. Enhanced views of the attic were demonstrated by the endoscope, further indicating utility in cholesteatoma observation and surgery. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s00405-020-05900-4) contains supplementary material, which is available to authorized users.